Ralstonia pickettii Bacteremia in Hemodialysis Patients - Gunbey, Fatma; Toraman, Zulal Asci; Genc, Fatih (Bilimsel Tip Yayinevi, 2023)
Ralstonia pickettii is an uncommon gram-negative bacillus that causes nosocomial infections, especially in immunocompromised patients. It is a water-based microorganism that can live in any water source and contaminate intravenous drugs, blood culture bottles, distilled water, saline solutions, and other solutions used for patient care in hospitals. In addition, Ralstonia pickettii can form and maintain a biofilm in plastic industrial water pipes. Nosocomial outbreaks of Ralstonia pickettii infections caused by the use of contaminated medical solutions, including saline solutions, distilled water, and disinfectants, have been reported. Here, we present three cases of catheter-related bloodstream infection caused by Ralstonia pickettii in patients receiving hemodialysis treatment at a different center. Many cases of infection with Ralstonia spp. are reported to be the result of colonization from contaminated solutions, blood products, chlorhexidine, saline solutions, sterile water, and medical devices. When bacteremia due to Ralstonia pickettii is identified, medicinal product contamination should be suspected and an epidemiological investigation should be initiated, including microbiological examination of administered fluids, drugs, and hemodialysis water.
Keywords: Ralstonia pickettii; MALDI-TOF MS; Bacteremia